AN INVESTIGATION OF ENGLISH SPEAKING SKILLS PERFORMANCE OF INTROVERT STUDENTS IN SPEAKING CLASS - Ferizka Emirza; Mohamad Sahril (ENGLISH, 2021)
This research aims to know the personality (introvert) affects the students on their speaking English performance and influences the students in their communication,and to know the effort of the introvert students to handle the personality problem inspeaking English performance. In order to collect the data, observation,questionnaire and interview was three research instrument used.The participant of this research was a 26 students in the second semester of EnglishEducation Department, Ibn Khaldun University Bogor. Finally for the result of thisresearch revealed that for the score was 2.23 in average of students speakingperformance, it means fair slightly good. This statement was strengthened with thedata analysis that the most affecting factors from psychological aspects towardsintrovert students in speaking skill were depressed (92%). From the linguisticsfactors, eight of thirteen students said vocabulary and grammar was the commonproblem. And six of thirteen students experienced difficulties in pronunciation.Introvert students used a various strategies to overcome their public speakingproblems, several students try to improving their speak ability by read a book andrecord it, sing an English song, have a conversation every day, by join thecommunity outside of the university, help their brother/sister do their homework,talk with the foreigner, watch YouTube.